Thin film magnetic anisotropy angle resolution measurement method based on tilt angle acrylic column
Patent Information
- Application Number
- CN202611163269.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-03
- Publication Date
- 2026-10-09
AI Technical Summary
以Quantum Design MPMS系列设备配套水平旋转杆、矢量磁场选件为例,该类高端配件采购成本高昂;国内多数高校、科研院所配置的第二代SQUID-VSM系统服役年限久,若需加装水平旋转功能,需更换马达和SQUID探测器等核心部件,改造成本高昂
[0015]本发明的优点和积极效果是:
Smart Images

Figure CN122883065A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of precision testing technology for magnetic thin film properties. Specifically, it relates to a method for angularly resolved spatial magnetic anisotropy testing of thin films that is compatible with commercial SQUID-VSM systems and requires no modification to the instrument hardware. It can be used for characterization and analysis of low-temperature hysteresis loops, coercivity, remanence, exchange bias effect, and magnetization reversal dynamics of anti-spinel oxide thin films, ferromagnetic / ferrimagnetic thin films, magnetic multilayer films, and topological magnetic thin films. Background Technology
[0002] Magnetic anisotropy is one of the important physical properties of magnetic materials, determining the preferred orientation of magnetic moments and playing a crucial role in the performance of magnetic devices. With the rapid development of magnetic topological materials, spintronics, and magnetic storage devices, accurate characterization of the magnetic anisotropy of thin film materials has become particularly important. Especially in emerging materials such as magnetic topological insulators and Weyl half-metals, magnetic anisotropy not only affects the stability and transport properties of topological states but is also closely related to physical mechanisms such as spin-orbit coupling.
[0003] Magnetic anisotropy determines the preferred arrangement of magnetic moments within magnetic materials and is a core physical property parameter for designing magnetic storage and spintronic devices. Superconducting quantum interference device-vibrating sample magnetometer (SQUID-VSM) is currently the mainstream instrument for quantitative characterization of thin-film magnetism. However, it can only measure hysteresis loops in two directions: in-plane and out-of-plane. It cannot obtain magnetization data when the magnetic field is at an arbitrary angle to the thin-film plane, making it difficult to analyze the spatial evolution of the magnetic moment vector. This restricts the quantitative fitting of anisotropy and the in-depth study of the microscopic mechanism of magnetization reversal.
[0004] Currently, the mainstream solution for achieving angle-resolved magnetic measurements is to purchase original manufacturer rotating sample stages and vector magnetic field modules. Taking the Quantum Design MPMS series equipment with its horizontal rotating rod and vector magnetic field option as an example, the procurement cost of such high-end components is high. The second-generation SQUID-VSM systems configured in most universities and research institutes in China have been in service for a long time. If horizontal rotation function is to be added, core components such as motors and SQUID detectors need to be replaced, resulting in high modification costs. Existing simple angle-resolved testing fixtures generally have drawbacks such as high substrate magnetic backing, easy deformation and cracking in the liquid helium temperature range, poor sample adhesion and sealing, cumbersome processing, and non-reusability.
[0005] Therefore, developing a thin-film magnetic anisotropy angle-resolved measurement method that requires no modification to existing magnetic testing instrument hardware, has low preparation cost, stable structure at low temperatures, low background interference, and reusable tooling is a practical engineering problem that urgently needs to be solved in the field of magnetic materials testing. Summary of the Invention
[0006] The purpose of this invention is to overcome the shortcomings of the prior art and provide a method for measuring the magnetic anisotropy angle of thin films based on tilted acrylic columns. The method uses CNC machining to prepare tilted acrylic wedge columns as the bearing fixture for the thin film under test. By simply changing the carrier with different tilt angles, quasi-continuous angle magnetic tests from 0° to 90° can be completed. No hardware modifications are required to the SQUID-VSM host throughout the process. It has the advantages of low processing cost, excellent low temperature stability, low magnetic background noise, simple operation, reusable fixture, and strong versatility.
[0007] The technical problem solved by this invention is achieved through the following technical solution: A method for angularly resolved measurement of thin-film magnetic anisotropy based on tilted acrylic pillars includes the following steps: S1. Processing and preparing multiple sets of acrylic wedge-shaped columns with different inclination angles: The acrylic wedge-shaped column is a right-angled wedge structure, including a mounting base, an inclined test surface, and a vertical surface. The angle between the inclined test surface and the mounting base is a preset test tilt angle. θ ; S2. Pre-treatment for cleaning acrylic wedge-shaped columns: The prepared acrylic wedge column was sequentially ultrasonically cleaned with acetone, anhydrous ethanol, and deionized water, and then dried with nitrogen gas for later use. S3. Assembly and curing of the thin film to be tested on the quartz rod: The acrylic wedge post was fixed to the quartz rod of the SQUID-VSM using low-temperature adhesive, and then the film to be tested was bonded and fixed to the inclined test surface of the acrylic wedge post. The film was left to stand at room temperature until the low-temperature adhesive was completely cured. S4. Acquisition and calibration of low-temperature magnetization data for thin films at different tilt angles: The quartz rod containing the thin film to be tested is inserted into the SQUID-VSM cavity. The test temperature and magnetic field scanning parameters are set. Acrylic wedges with different tilt angles are used to collect the original magnetization data of the thin film at each tilt angle from 0° to 90°. The magnetic curve of the acrylic wedge is tested in advance to calibrate the back surface signal of the acrylic itself. S5. Back-ground correction processing of raw test data to extract intrinsic magnetic parameters of the thin film under test: Background correction was performed on the collected raw magnetization data: the equivalent diamagnetic susceptibility of the system was selected by fitting the data of the high field region of the magnetization curve, the corresponding background magnetization intensity was calculated, the background signal was subtracted from the raw data to obtain the true hysteresis loop of the thin film, and the coercivity and remanence parameters were extracted to analyze the angular evolution law of magnetic anisotropy. S6. After the test is completed, the film under test, acrylic wedge, and quartz rod are disassembled, recycled, and reused. After the test, the quartz rod was immersed in anhydrous ethanol to achieve desorption and separation of the test film and the acrylic wedge column. The film was recovered and stored, and the acrylic wedge column and quartz rod were cleaned and reused.
[0008] Furthermore, the acrylic wedge-shaped column is prepared by CNC machining, laser cutting or 3D printing, the substrate is PMMA organic glass, and the mounting bottom surface, inclined test surface and vertical surface of the column are all mirror polished, and the roughness Ra after the inclined surface is polished is ≤0.8μm.
[0009] Furthermore, the acrylic wedge-shaped column prepared in step S1 has an inclination gradient of 10°, 20°, 30°, 40°, 50°, 60°, 70°, and 80°; for the 0° in-plane test, the film is directly bonded to the surface of the quartz rod, and for the 90° out-of-plane test, the film is bonded to the vertical surface of the acrylic column.
[0010] Furthermore, the ultrasonic cleaning time for each solvent in step S2 is 10 min.
[0011] Furthermore, the low-temperature adhesive used in step S3 is GE Varnish 7031 low-temperature adhesive, and the room temperature curing time of the adhesive is 20~40 min.
[0012] Furthermore, in step S5, the high-field range selected for fitting the equivalent diamagnetic susceptibility is 0.7 T to 1 T.
[0013] Furthermore, the acrylic wedge-shaped column has a magnetization of -1.0 × 10⁻⁶ at 5 K. -4 emu, the magnetization at 300 K is -1.8 × 10⁻⁶. -4 emu exhibits stable antimagnetic properties throughout the entire process.
[0014] Furthermore, this method is applicable to the testing and characterization of low-temperature angle-resolved hysteresis loops, exchange bias effects, and magnetic anisotropy evolution behavior of ferromagnetic thin films, subferromagnetic oxide thin films, magnetic multilayer films, and topological magnetic thin films.
[0015] The advantages and positive effects of this invention are: 1. The present invention is a thin-film magnetic anisotropy angle resolution measurement method based on tilted acrylic columns. By modifying the hardware acrylic columns, the upgrade cost is reduced: the original SQUID-VSM hardware system is used throughout the process, without the need to replace core components such as motors and SQUID detectors, thus avoiding the high procurement and modification costs of original factory parts and reducing costs.
[0016] 2. This invention is based on a thin-film magnetic anisotropy angle resolution measurement method using tilted acrylic columns. The acrylic wedge columns are manufactured using mature CNC mass production technology with low processing costs. After testing, the acrylic wedge columns can be cleaned and reused repeatedly, significantly reducing the cost of long-term experiments.
[0017] 3. The present invention provides a thin film magnetic anisotropy angle resolution measurement method based on tilted acrylic columns. The test data has high accuracy, background interference is controllable, the intrinsic diamagnetic signal of PMMA substrate is weak and the temperature stability is good, the polished inclined surface ensures gapless bonding of the film, and with the high field linear fitting background subtraction algorithm, the intrinsic magnetization behavior of the film can be accurately restored.
[0018] 4. The present invention is based on the thin film magnetic anisotropy angle resolution measurement method of tilted acrylic column. It has strong adaptability to low temperature environment. Acrylic does not have cracking, deformation or swelling problems in the liquid helium extremely low temperature range. It has stable chemical properties and is suitable for various low temperature magnetic test scenarios.
[0019] 5. The present invention provides a method for measuring the magnetic anisotropy angle of thin films based on tilted acrylic columns. It is easy to operate and has wide material applicability. Quasi-continuous angle testing can be completed simply by changing the tilted columns. It is applicable to the magnetic anisotropy testing of ferromagnetic thin films, ferrimagnetic oxide thin films, magnetic multilayer films, and topological magnetic thin films. Attached Figure Description
[0020] Figure 1 (a) is a schematic diagram of the acrylic wedge-shaped column of the present invention; Figure 1 (b) is a solid drawing of the acrylic wedge-shaped column of the present invention at a 50° tilt angle; Figure 1 (c) is a schematic diagram of the thin film assembly geometry of the present invention; Figure 2 This is a magnetization response curve of the acrylic wedge-shaped column of the glass substrate of the present invention; Figure 3 (a) is a crystal structure diagram of the NiCo2O4 anti-spinel of the present invention; Figure 3 (b) is the X-ray diffraction pattern of the NiCo2O4 thin film of the present invention; Figure 4 The hysteresis loop spectra of the NiCo2O4 thin film at 10 K temperature corresponding to different tilt angles from 0° to 90° are shown below. Figure 5 (a) is a graph showing the relationship between the coercivity of the NiCo2O4 thin film of the present invention and the tilt angle under positive and negative magnetic fields; Figure 5 (b) is a graph showing the relationship between the remanence of the NiCo2O4 thin film of the present invention and the tilt angle under positive and negative magnetic fields. Detailed Implementation
[0021] The present invention will be further described in detail below through specific embodiments. The following embodiments are merely descriptive and not limiting, and should not be used to limit the scope of protection of the present invention.
[0022] The NiCo2O4 thin film was epitaxially grown on a MgAl2O4 (MAO) substrate by pulsed laser deposition, with a thickness of approximately 43 nm. Figure 3 (b) XRD measurement results show that NiCo2O4 mainly grows along the (001) direction. The complete implementation steps for angularly resolved magnetic anisotropy measurements at 10K temperature from 0° to 90° are as follows: NiCo2O4 is a transition metal oxide with an inverse spinel structure, and its crystal structure is as follows: Figure 3 As shown in (a), NiCo2O4 thin films, as a representative strongly correlated transition metal oxide material, have attracted widespread attention in condensed matter physics and spintronics in recent years due to their excellent electrical transport properties, room-temperature magnetic ordering characteristics, and abundant spin modulation degrees of freedom. However, their magnetic properties are strongly dependent on the orientation of the magnetic field relative to the film plane, and traditional methods that only measure the two extreme angles of in-plane and out-of-plane are insufficient to fully reveal the essential characteristics of their magnetic anisotropy. Therefore, systematically studying the magnetization behavior of NiCo2O4 thin films under different magnetic field tilt angles is of great significance for a deeper understanding of the origin of their perpendicular magnetic anisotropy, the mechanism of magnetic moment rotation, and their potential spintronics applications.
[0023] like Figure 1 As shown in (c), a method for angle-resolved measurement of thin film magnetic anisotropy based on tilted acrylic columns is described. The entire test is conducted using a commercial SQUID-VSM system without hardware modifications. The external magnetic field is fixedly arranged along the axis of the quartz sample rod. The angle-resolved measurement is achieved by changing the angle between the plane of the thin film under test and the external magnetic field through acrylic wedge columns with different tilt angles. The method includes the following steps: S1. Processing and preparing multiple sets of acrylic wedge-shaped columns with different inclination angles: like Figure 1 As shown in (a) and (b), the acrylic wedge column is a right-angled wedge structure, including a mounting base, an inclined test surface, and a vertical surface. The angle between the inclined test surface and the mounting base is a preset test inclination angle θ. The acrylic wedge column is prepared by CNC machining, laser cutting, or 3D printing. The substrate is PMMA organic glass. The mounting base, inclined test surface, and vertical surface of the column are all mirror polished. The roughness Ra after the inclined surface is polished is ≤0.8μm. The inclination angle gradient of the acrylic wedge column is 10°, 20°, 30°, 40°, 50°, 60°, 70°, and 80°. For the 0° in-plane test, the film is directly bonded to the surface of the quartz rod. For the 90° out-of-plane test, the film is bonded to the vertical surface of the acrylic column.
[0024] PMMA possesses extremely weak intrinsic diamagnetism, exhibiting stable magnetization signals with very low amplitudes at room temperature and in the liquid helium temperature range. This minimizes interference with the magnetic signals of the thin films under test, effectively avoiding background noise. It also boasts excellent machinability and low cost for mass production. Its low density and light weight ensure that its assembly onto a quartz rod does not increase the load on the vibration system, maintaining the original testing accuracy of the equipment. Furthermore, its good chemical stability prevents cracking and deformation under liquid helium cryogenic conditions, making it suitable for the entire process of low-temperature adhesive bonding and organic solvent disassembly. The smooth surface and light-transmitting properties of the material facilitate visual alignment and calibration during the bonding process of the thin films under test.
[0025] S2. Pre-treatment for cleaning acrylic wedge-shaped columns: The prepared acrylic wedge column was ultrasonically cleaned stepwise with acetone, anhydrous ethanol, and deionized water. After cleaning, it was dried with nitrogen gas for later use. The ultrasonic cleaning time for each solvent was 10 min.
[0026] Remove residual oil and surface dust from the column processing to avoid introducing additional magnetic back noise from impurities. S3. Assembly and curing of the thin film to be tested on the quartz rod: A 50° angled acrylic wedge post was fixed to the quartz rod of the SQUID-VSM using low-temperature adhesive. The film to be tested was then bonded and fixed to the inclined test surface of the acrylic wedge post. The film was left to stand at room temperature until the low-temperature adhesive was completely cured. GE Varnish 7031 low-temperature adhesive was selected as the bonding medium. Assembly and curing steps: S301: Use a toothpick to evenly apply the low-temperature adhesive to the calibration installation area of the SQUID-VSM matching quartz rod; S302: Use plastic tweezers to hold the dried acrylic wedge and attach it to the adhesive surface. Apply slight pressure to firmly bond the acrylic wedge to the quartz rod. S303: Apply a thin, uniform layer of low-temperature adhesive to the inclined test surface of the acrylic wedge-shaped column; S304: Use plastic tweezers to pick up the film to be tested, lay it flat and adhere it to the inclined test surface, and gently press the four corners of the sample to remove air bubbles in the adhesive layer, so as to achieve a tight and gapless adhesion between the film and the inclined surface; S305: After assembly, place the quartz rod horizontally for 20 to 40 minutes to allow the low-temperature adhesive to fully cure, thus completing the assembly of the test sample tooling. Angle adaptation rules: For 0° in-plane testing, the film to be tested is directly pasted onto the surface of the quartz rod; for 90° out-of-plane testing, the film to be tested is bonded and fixed onto the vertical surface of the acrylic wedge column.
[0027] S4. Acquisition and calibration of low-temperature magnetization data for thin films at different tilt angles: The quartz rod containing the thin film to be tested is installed into the SQUID-VSM cavity. The test temperature is set to 10 K and the magnetic field scanning range is 0.7 T to 1 T. Acrylic wedge columns with different tilt angles are replaced in turn to collect the original hysteresis loop data of the thin film to be tested corresponding to each tilt angle from 0° to 90°. like Figure 2 As shown, the magnetic curves of acrylic wedge-shaped pillars on glass substrates were pre-tested to calibrate the diamagnetic backplane signal of the acrylic substrate. The ZFC-FC curves under a 1T magnetic field and the magnetization curves at 5 K and 300 K were also tested to calibrate the diamagnetic backplane signal of the acrylic substrate. The test results show that the acrylic wedge-shaped pillar substrates all exhibit typical diamagnetic behavior, and the diamagnetic signal intensity increases with increasing temperature. At 5 K, the acrylic magnetization intensity is approximately -1.0 × 10⁻⁶. -4 emu, magnetization at 300 K is approximately -1.8 × 10⁻⁶. -4 emu has a weak, stable, and repeatable magnetic signal.
[0028] S5. Back-ground correction processing of raw test data to extract intrinsic magnetic parameters of the thin film under test: Background correction was performed on the collected raw magnetization data: the equivalent diamagnetic susceptibility of the system was selected by fitting the data of the high field region of the magnetization curve, the corresponding background magnetization intensity was calculated, the background signal was subtracted from the raw data to obtain the true hysteresis loop of the thin film, and the coercivity and remanence parameters were extracted to analyze the angular evolution law of magnetic anisotropy. S501: Select the data from the 0.7 T to 1 T high-field linear range of each magnetization curve for linear fitting, and solve the overall equivalent diamagnetic susceptibility of the system; S502: Combine the real-time magnetic field strength and the equivalent diamagnetic susceptibility to calculate the overall back-bottom magnetization intensity corresponding to each tilt angle; S503: Subtract the corresponding background value from the original magnetization data to eliminate all diamagnetic background interference and obtain a pure true hysteresis loop of the thin film under test. Based on the corrected curves, parameters such as coercivity, remanent magnetization, hysteresis rectangularity, and exchange bias field at different tilt angles are extracted to analyze the dynamic evolution of thin film magnetic anisotropy with tilt angle.
[0029] like Figure 4 As shown, the test results indicate that the hysteresis loop of the NiCo2O4 thin film at 10 K exhibits typical strong perpendicular magnetic anisotropy. As the magnetic field inclination angle increases from 0° (in-plane, difficult-to-magnetize axis) to 90° (perpendicular to the film surface, easy-to-magnetize axis), the loop gradually transforms from an inclined, difficult-to-saturate shape into a square loop with high rectangularity and a steep shape, with a significant increase in the coercive field. This evolution clearly reflects the rotation of the magnetic moment from the in-plane difficult axis to the easy axis. The loop at 90° has the highest squareness and remanence, indicating that the easy-to-magnetize axis of the thin film is perpendicular to the film surface.
[0030] Magnetization curves can be used to extract the coercivity of NiCo2O4 thin films under positive and negative magnetic fields. H c (θ) and remanent magnetization M r (θ) Relationship with tilt angle. Here, to facilitate comparison of the differences between coercivity and remanent magnetization under positive and negative magnetic fields, we take the absolute value of the negative field, and the results are as follows. Figure 5 As shown in (a) and (b), it can be seen that the coercivity of the positive magnetic field (+ H c ) and the absolute value of the coercivity of the negative magnetic field (|- H c At small angles (near the in-plane), significant differences exist, reflecting exchange bias or unidirectional anisotropy effects; however, as the tilt angle increases to the vertical direction, the positive and negative coercive forces tend to be symmetrical, reaching their maximum value. Remanence M r It also exhibits a strong angle dependence, rapidly increasing from a small value in the plane to a maximum value in the vertical direction, further confirming the existence of uniaxial perpendicular magnetic anisotropy. This separate presentation of positive and negative field magnetic parameters accurately reveals the differences in magnetization reversal mechanisms under different magnetic field orientations, providing direct data support for the systematic study of the dynamic evolution of magnetic anisotropy.
[0031] When the magnetic field tilt angle increases from 0° to 90°, the hysteresis loop gradually changes from a tilted, gradually changing shape to a highly rectangular square loop. The coercivity and remanent magnetization increase significantly with the increase of the tilt angle. There is a difference between the positive and negative coercivity in the small angle range, which indicates that there is an exchange bias effect in the system. The magnetic parameters in the direction perpendicular to the film surface tend to be symmetrical and reach their peak value. This directly characterizes the dynamic evolution process of the vertical magnetic anisotropy of the thin film and verifies that the measurement method is accurate and reliable.
[0032] S6. After the test is completed, the film under test, acrylic wedge, and quartz rod are disassembled, recycled, and reused. S601: After the test, the quartz rod is removed and immersed in anhydrous ethanol solution. Relying on the characteristic that GE 7031 low-temperature adhesive is soluble in ethanol, the test film and acrylic wedge column are automatically desorbed and separated. S602: After separation, the test film is allowed to stand to evaporate the ethanol and then sealed for storage; the acrylic wedge column is ultrasonically cleaned with ethanol and deionized water and dried with nitrogen before being reused; the quartz rod is wiped clean with anhydrous ethanol and then stored.
[0033] Although embodiments and drawings of the present invention have been disclosed for illustrative purposes, those skilled in the art will understand that various substitutions, variations and modifications are possible without departing from the spirit and scope of the present invention and the appended claims. Therefore, the scope of the present invention is not limited to the contents disclosed in the embodiments and drawings.
Claims
1. A method for resolving the angle of magnetic anisotropy of thin films based on tilted acrylic columns, characterized in that: Includes the following steps: S1. Processing and preparing multiple sets of acrylic wedge-shaped columns with different inclination angles: The acrylic wedge-shaped column is a right-angled wedge structure, including a mounting base, an inclined test surface, and a vertical surface. The angle between the inclined test surface and the mounting base is a preset test tilt angle. θ ; S2. Pre-treatment for cleaning acrylic wedge-shaped columns: The prepared acrylic wedge column was sequentially ultrasonically cleaned with acetone, anhydrous ethanol, and deionized water, and then dried with nitrogen gas for later use. S3. Assembly and curing of the thin film to be tested on the quartz rod: The acrylic wedge post was fixed to the quartz rod of the SQUID-VSM using low-temperature adhesive, and then the film to be tested was bonded and fixed to the inclined test surface of the acrylic wedge post. The film was left to stand at room temperature until the low-temperature adhesive was completely cured. S4. Acquisition and calibration of low-temperature magnetization data for thin films at different tilt angles: The quartz rod containing the thin film to be tested is inserted into the SQUID-VSM cavity. The test temperature and magnetic field scanning parameters are set. Acrylic wedges with different tilt angles are used to collect the original magnetization data of the thin film at each tilt angle from 0° to 90°. The magnetic curve of the acrylic wedge is tested in advance to calibrate the back surface signal of the acrylic itself. S5. Back-ground correction processing of raw test data to extract intrinsic magnetic parameters of the thin film under test: Background correction was performed on the collected raw magnetization data: the equivalent diamagnetic susceptibility of the system was selected by fitting the data of the high field region of the magnetization curve, the corresponding background magnetization intensity was calculated, the background signal was subtracted from the raw data to obtain the true hysteresis loop of the thin film, and the coercivity and remanence parameters were extracted to analyze the angular evolution law of magnetic anisotropy. S6. After the test is completed, the film under test, acrylic wedge, and quartz rod are disassembled, recycled, and reused. After the test, the quartz rod was immersed in anhydrous ethanol to achieve desorption and separation of the test film and the acrylic wedge column. The film was recovered and stored, and the acrylic wedge column and quartz rod were cleaned and reused.
2. The method for measuring the angle-resolved magnetic anisotropy of thin films based on tilted acrylic columns according to claim 1, characterized in that: The acrylic wedge-shaped column is manufactured by CNC machining, laser cutting or 3D printing. The substrate is PMMA organic glass. The mounting bottom surface, inclined test surface and vertical surface of the column are all mirror polished. The roughness Ra after the inclined surface is polished is ≤0.8μm.
3. The method for measuring the angle-resolved magnetic anisotropy of thin films based on tilted acrylic columns according to claim 1, characterized in that: The acrylic wedge-shaped columns prepared in step S1 have tilt angle gradients of 10°, 20°, 30°, 40°, 50°, 60°, 70°, and 80°. For the 0° in-plane test, the film is directly bonded to the surface of the quartz rod, and for the 90° out-of-plane test, the film is bonded to the vertical surface of the acrylic column.
4. The method for measuring the angle-resolved magnetic anisotropy of thin films based on tilted acrylic columns according to claim 1, characterized in that: The ultrasonic cleaning time for each solvent in step S2 is 10 min.
5. The method for measuring the angle-resolved magnetic anisotropy of thin films based on tilted acrylic columns according to claim 1, characterized in that: The low-temperature adhesive used in step S3 is GE Varnish 7031 low-temperature adhesive, and the curing time of the adhesive at room temperature is 20~40 min.
6. The method for measuring the angle-resolved magnetic anisotropy of thin films based on tilted acrylic columns according to claim 1, characterized in that: In step S5, the high-field range selected for fitting the equivalent diamagnetic susceptibility is 0.7 T to 1 T.
7. The method for resolving the angle of magnetic anisotropy of thin films based on tilted acrylic columns according to claim 1, characterized in that: The acrylic wedge-shaped column has a magnetization of -1.0 × 10⁻⁶ at 5 K. -4 emu, the magnetization at 300 K is -1.8 × 10⁻⁶. -4 emu exhibits stable antimagnetic properties throughout the entire process.
8. The method for measuring the angle-resolved magnetic anisotropy of thin films based on tilted acrylic columns according to claim 1, characterized in that: This method is applicable to the testing and characterization of low-temperature angle-resolved hysteresis loops, exchange bias effects, and magnetic anisotropy evolution behavior of ferromagnetic thin films, subferromagnetic oxide thin films, magnetic multilayer films, and topological magnetic thin films.